Virulence and Antibiotic Resistance Profiles of Cronobacter sakazakii and Enterobacter spp. Involved in the Diarrheic Hemorrhagic Outbreak in Mexico - Parra-Flores, Julio; Aguirre, Juan; Juneja, Vijay; Jackson, Emily E.; Cruz-Córdova, Ariadnna; Silva-Sanchez, Jesus; Forsythe, Stephen (Frontiers in Microbiology, 2018)
Cronobacter spp. are bacterial pathogens that cause neonatal meningitis, septicemia, and necrotizing enterocolitis in infants with a lethality rate of 40-80%. Powdered infant formulas (PIF) have been implicated as the main vehicles of transmission. The organism can also cause infection through contaminated expressed breast milk, and has been recovered from neonatal feeding tubes of neonates not fed reconstituted PIF. This study analysed Cronobacter sakazakii and Enterobacter spp. recovered from PIF, fecal matter, and the milk kitchen environment from an diarrheic hemorrhagic outbreak in 2011 in Mexico, with respect to their tissue virulence tests, and antibiotic resistance profiles. These strains had similar pathogenicity and antibiotic resistance profiles irrespective of isolation site.